Influence of Bionic Pit Structure on Friction and Sealing Performance of Reciprocating Plunger - Tianyu Gao; Bo Su; Lei Jiang; Qian Cong (Advances in Materials Science and Engineering)
A new kind of pit-shaped bionic plunger proposes to reduce the frictional resistance of the reciprocating plunger and improve its sealing performance. According to the dorsal pore of earthworm, the bionic pit structure with different parameters designed and processed. The friction resistance test, observation test, and finite element analysis carried out. The results show that the bionic pit structure can improve the lubrication condition of the plunger surface and reduce the frictional resistance with a maximum drag reduction rate of 14.32%. The pit-shaped bionic structure can increase the storage of lubricating oil, intercept the surface streamline, and decrease the flow rate. The bionic plungers’ mean contact pressure and oil film pressure increased significantly.